Durability of ChAdOx1 nCov-19 vaccination in people living with HIV - Ogbe, A; Pace, M; Bittaye, M; Tipoe, T; Adele, S; Alagaratnam, J; Aley, PK; Ansari, MA; Bara, A; Broadhead, S; Brown, A; Brown, H; et al. (American Society for Clinical Investigation, 2022)
Duration of protection from SARS-CoV-2 infection in people with HIV (PWH) following vaccination is unclear. In a sub-study of the phase 2/3 the COV002 trial (NCT04400838), 54 HIV positive male participants on antiretroviral therapy (undetectable viral loads, CD4+ T cells >350 cells/ul) received two doses of ChAdOx1 nCoV-19 (AZD1222) 4-6 weeks apart and were followed for 6 months. Responses to vaccination were determined by serology (IgG ELISA and MesoScale Discovery (MSD)), neutralisation, ACE-2 inhibition, gamma interferon ELISpot, activation-induced marker (AIM) assay and T cell proliferation. We show that 6 months after vaccination the majority of measurable immune responses were greater than pre-vaccination baseline, but with evidence of a decline in both humoral and cell mediated immunity. There was, however, no significant difference compared to a cohort of HIV-uninfected individuals vaccinated with the same regimen. Responses to the variants of concern were detectable, although were lower than wild type. Pre-existing cross-reactive T cell responses to SARS-CoV-2 spike were associated with greater post-vaccine immunity and correlated with prior exposure to beta coronaviruses. These data support the on-going policy to vaccinate PWH against SARS-CoV-2, and underpin the need for long-term monitoring of responses after vaccination.